A importância da caracterização do módulo de elasticidade e do amortecimento de refratários por técnica dinâmica - Exposito, Caio Cesar Dente (2013)
This dissertation tries to understand the mechanisms involving damping phenomenon in ceramic refractory materials, using a dynamic technique. Damping proves to be an interesting parameter to analyze thermal shock damage in these sorts of materials. This technique would make possible to compare damping measurements with well-established techniques, such as the determination of modulus of elasticity modulus and modulus of rupture. Furthermore, this study attempts to understand the nonlinear phenomenon in damping and modulus of elasticity that depends on the vibrational amplitude. Aiming to understand how the variation on the vibration amplitude affects the mzasured values of damping and modulus of elasticity and how the nonlinear effect can be used in our advantage and in industrial daily routine, such as determining whether samples are damaged or not without a previous analysis or a standard material for reference. This study also approaches the influence of water in the nonlinear behavior of damping and modulus of elasticity. Thus, it would be possible to establish trustable and standardize procedures to measure those. In addition it would be possible to understand the drying process of ceramic refractory castables.